Long‐term clinical course of idiopathic pulmonary haemosiderosis with rheumatoid arthritis. Issue 5 (4th July 2016) - Sugimoto, Shunsuke; Terada, Jiro; Naito, Akira; Nishimura, Rintaro; Tsushima, Kenji; Tatsumi, Koichiro
Abstract : Idiopathic pulmonary haemosiderosis (IPH) is a rare cause of diffuse alveolar haemorrhage during childhood, and its precise pathophysiology and long‐term clinical course remain unclear. A 31‐year‐old man was diagnosed with IPH at four years of age and had recurrent episodes of haemoptysis. The patient's symptoms responded well to steroids. However, pulmonary fibrosis and the cystic region in the lung progressively worsened. At age 27, the patient developed polyarthritis with positive anti‐cyclic citrullinated peptide antibodies. The patient also developed hand synovitis, which was diagnosed with ultrasonography. These results indicate complications from rheumatoid arthritis. The patient's dyspnoea gradually worsened, and at the age of 31, he developed pneumothorax and an acute exacerbation of IPH. The clinical course from ages 4 to 31 included progressive chronic respiratory failure because of pulmonary fibrosis, acute exacerbations, complications with rheumatoid arthritis, and deliberation regarding lung transplantation. The development of rheumatoid arthritis after the onset of IPH supports the theory of an autoimmune mechanism of IPH. Abstract : Idiopathic pulmonary hemosiderosis (IPH) is a rare disease characterized by recurrent episodes of diffuse alveolar hemorrhage. In this case study, we describe an IPH patient who developed rheumatoid arthritis, pneumothorax, and respiratory failure more than 20 years after the initial diagnosis.